Cathepsin B induces kidney diseases through different types of programmed cell death - Zhao, Yunlong; Zhuang, Yong; Shi, Jie; Fan, Haojun; Lv, Qi; Guo, Xiaoqin (Frontiers in Immunology, 2025)
Cathepsin B (CTSB), a key cysteine protease, plays essential roles in physiological and pathological processes. As research progresses, interest in how CTSB triggers different types of programmed cell death (PCD) to induce the onset and development of diseases is increasing. Several recent studies suggest that different types of PCD mediated by CTSB play key roles in kidney diseases. In this review, we outline the fundamental mechanisms by which CTSB triggers different types of PCD in several kidney diseases and discuss the function of CTSB in various segments of the kidney. Moreover, we explore the possibilities and prospects of using CTSB as a therapeutic target for kidney diseases.